Fibroblast activation protein is induced by inflammation and degrades type I collagen in thin-cap fibroatheromata - Brokopp, Chad E.; Schoenauer, Roman; Richards, Peter; Bauer, Stefan; Lohmann, Christine; Emmert, Maximilian Y.; Weber, Benedikt; Winnik, Stephan Hendrik; Aikawa, Elena; Graves, Kirk; Genoni, Michele; Vogt, Peter; et al. (European heart journal, 2011)
Collagen degradation in atherosclerotic plaques with thin fibrous caps renders them more prone to rupture. Fibroblast activation protein (FAP) plays a role in arthritis and tumour formation through its collagenase activity. However, the significance of FAP in thin-cap human fibroatheromata remains unknown.We detected enhanced FAP expression in type IV-V human aortic atheromata (n = 12), compared with type II-III lesions (n = 9; P < 0.01) and healthy aortae (n = 8; P < 0.01) by immunostaining and western blot analyses. Fibroblast activation protein was also increased in thin-cap (<65 µm) vs. thick-cap (≥65 µm) human coronary fibroatheromata (n = 12; P < 0.01). Fibroblast activation protein was expressed by human aortic smooth muscle cells (HASMC) as shown by colocalization on immunofluorescent aortic plaque stainings (n = 10; P < 0.01) and by flow cytometry in cell culture. Although macrophages did not express FAP, macrophage burden in human aortic plaques correlated with FAP expression (n = 12; R2= 0.763; P < 0.05). Enzyme-linked immunosorbent assays showed a time- and dose-dependent up-regulation of FAP in response to human tumour necrosis factor α (TNFα) in HASMC (n = 6; P < 0.01). Moreover, supernatants from peripheral blood-derived macrophages induced FAP expression in cultured HASMC (n = 6; P < 0.01), an effect abolished by blocking TNFα (n = 6; P < 0.01). Fibroblast activation protein associated with collagen-poor regions in human coronary fibrous caps and digested type I collagen and gelatin in vitro (n = 6; P < 0.01). Zymography revealed that FAP-mediated collagenase activity was neutralized by an antibody directed against the FAP catalytic domain both in HASMC (n = 6; P < 0.01) and in fibrous caps of atherosclerotic plaques (n = 10; P < 0.01).Fibroblast activation protein expression in HASMC is induced by macrophage-derived TNFα. Fibroblast activation protein associates with thin-cap human coronary fibroatheromata and contributes to type I collagen breakdown in fibrous caps.